PENGARUH KUALITAS WEBSITE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA SITUS LAMUDI.CO.ID - Ismail; Sinta Sulistiani (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of Website Quality and Promotion on Purchase Decisions on the Lamudi.co.id website, both partially and simultaneously. The method used is quantitative. Data collection techniques used questionnaires, with a population of 9,250 consumers. The sampling technique used Slovin’s formula, resulting in a sample of 99 consumers. Data analysis techniques included validity tests, reliability tests, classical assumption tests, regression analysis, determination coefficient analysis, and hypothesis testing. The results of this  study indicate that  Website Quality has  a  significant  effect  on  Purchase Decisions, with the regression equation Y = 10.492 + 0.723 X₁. With a correlation coefficient of 0.490, the two variables have a strong relationship. The coefficient of determination is 0.428, meaning that purchase decisions are influenced by Website Quality by 42.8%. The hypothesis test obtained a t-value > t-table (8.525 > 1.984), so H₀ is rejected and H₁ is accepted. Promotion also has a significant effect on Purchase Decisions, with the regression equation Y = 6.425 + 0.742 X₂. With a correlation coefficient of 0.388, the two variables have a strong relationship. The coefficient of determination is 0.489, meaning that purchase decisions are influenced by Promotion by 48.9%. The hypothesis test obtained a value of (9.629 > 1.984), so H₀ is rejected and H₂ is accepted. Website Quality and Promotion both significantly influence Purchase Decisions, with the regression equation Y = 2.119 + 0.393 X₁ + 0.505 X₂. With a correlation coefficient of 0.752, Website Quality and Promotion have a strong relationship with Purchase Decisions. The coefficient of determination is 0.566, meaning that purchase decisions are influenced by Website Quality and Promotion by 56.6%. The hypothesis test obtained an F-value > F- table (65.508 > 3.09). Thus, H₀ is rejected and H₃ is accepted.